الأركان العامة للجريمة في الفقه الإسلامي دراسة تحليلية - محمود, بإشراف: أ. م. د.عمر أحمد; أحمد, م. حامد سعيد (Sulaimani Journal for Humanities, 2023)
This research is entitled the pillars of crime in Islamic jurisprudence, and it consists of an introduction, a preface, three demands, and a conclusion. Through it, the meaning of the pillar was shown linguistically and legally, and it was also mentioned about the general elements of the crime, which must be present in order for the act or omission to be considered a crime, And it is represented in the legal pillar that there is a legal text that prohibits action or omission, and indicates the punitive penalty resulting from it, and the material pillar that it occurs from the criminal who made up the crime, whether it was action, omission or participation, and the moral pillar that responsibility for the matter that occurred takes place from the criminal who signed from him, Which is mentioned in the text to criminalize him and punish him, by providing the elements of moral responsibility in his person from awareness, will and choice, by relying on the analytical approach to clarify the path taken by Islamic law in criminalization and punishment, Sharia does not establish worldly criminal accountability except for the outward appearance of behavior, and limits this responsibility to a living, aware, chosen person who is able to carry out the responsibility and bear the consequences.
Keywords: Keywords elements of crime; crime; Islamic jurisprudence